Evidence-based practices in autism: where we started to where we are now - Reichow, B.; Doehring, P.; Volkmar, F.R. (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
When we published our first volume, the evidence-based practice (EBP) movement in the field of autism spectrum disorder (ASD) had already begun to gain strength around the world, and it has since shown no signs of abating. Multiple organizations and groups have now produced EBP guidelines concerning the treatment and/or identification of ASD. However, the resulting definitions continue to vary in important ways across professions and sometimes even within their subdivisions. A universal definition of EBP remains elusive. While these conclusions drawn from the previous edition of this book still hold true, we are nonetheless encouraged by the growth in interest in EBP and by the dramatic increase in the number of high-quality research studies over the past 15 years and so are excited to offer this updated and expanded handbook. This chapter serves as an introduction to the current state of affairs with respect to evidence-based practices in autism spectrum disorders. © Springer Nature Switzerland AG 2025.
Keywords: Evidence-based practice; History; Intervention; Practice guidelines; Treatment; dept.sed